2014
DOI: 10.1179/1743294414y.0000000275
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of rock salt AlN coatings by magnetron sputtering

Abstract: Cubic aluminium nitride (AIN) coatings were successfully deposited on stainless steel 304L substrates by balanced magnetron sputtering. Grazing incidence X-ray diffraction measurement confirmed the formation of rock salt cubic AIN having a preferred orientation along (111) plane. Scanning electron microscopy revealed nodular microstructure of the coating. Thermal diffusivity of AIN coated sample was found to be significantly higher than that of the uncoated sample. Microscratch adhesion test showed no adhesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…It is well known that in the case of balanced magnetron sputtering, the ion current drawn at the substrate is insufficient to modify the structure of the film. Therefore, the depositing species have a tendency to retain the structure of the substrate up to a few atomic layers, unless a high substrate bias voltage is applied [28,32]. The influence of substrate on the crystal structure of AlN coatings is further supported by the work of Ababneh et al [33], who reported c-axis oriented wurtzite AlN coatings on titanium.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations
“…It is well known that in the case of balanced magnetron sputtering, the ion current drawn at the substrate is insufficient to modify the structure of the film. Therefore, the depositing species have a tendency to retain the structure of the substrate up to a few atomic layers, unless a high substrate bias voltage is applied [28,32]. The influence of substrate on the crystal structure of AlN coatings is further supported by the work of Ababneh et al [33], who reported c-axis oriented wurtzite AlN coatings on titanium.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…However, limited literature is available on the deposition of cubic (zinc blende or rock salt) AlN coatings by magnetron sputtering. In our previous reported study [28], it was brought out that the cubic the growth of cubic phase AlN [28]. It is well known that in the case of balanced magnetron sputtering, the ion current drawn at the substrate is insufficient to modify the structure of the film.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…AlN films are widely used for surface acoustic wave (SAW), film bulk acoustic wave (FBAW) devices and some optical devices because of their high SAW velocity, suitable piezoelectric coupling factors, high hardness ([20 GPa), wide energy band gap (6.2 eV), and high thermal conductivity (3.9 W/cm K at RT) [1][2][3][4]. Meanwhile, aluminum nitride (AlN) thin films has become a standard electronic materials for many conventional MEMS devices, especially for high-temperature piezoelectric sensors and thin film bulk-acoustic resonator (FBAR) duplex filters for its excellent combination of remarkable properties.…”
Section: Introductionmentioning
confidence: 99%
“…This process of precipitation requires large amount of chromium and hence the chromium from the adjacent region diffuse resulting in the formation of chromium-depleted zone. This zone is anodic to the unaffected grains and consequently becomes a preferential site for corrosion attack or crack propagation under tensile stress.Presently various coating techniques such as oxidation of an evaporated metal film [5,6], reactive and non-reactive sputtering techniques [7], chemical vapor deposition [8], physical vapour deposition [9] and sol-gel coating [10] are employed to fabricate surface protective coatings for ferrous and non-ferrous alloys. Nevertheless, fabrication of nanocomposite coatings with required proportion of nanostructures like nanoparticles and nanorods of other elements by the above…”
mentioning
confidence: 99%